Las acciones de enfermería y su relación con la prevención de embarazos en adolescentes. unidad educativa Nicolás Infante Diaz del cantón Palenque. Los Ríos. primer semestre del 2018 - Mayra Alejandra, Loor Vivanco (2018)
Teen pregnancy continues to be a public health problem worldwide. Latin America and the Caribbean continue with the second highest rate of teen pregnancy. This continues to be one of the main factors that contribute to maternal and infant mortality. Adolescence is one of the most important stages of change in the life of the human being, characterized by growth and biological, psychological and social changes. It is important that health professionals give educational talks and guide students about sex education, to prevent future pregnancies in adolescents That is why the general objective was to identify the relationship of nursing actions with the prevention of pregnant women in adolescents in the Nicolás Infante Díaz del Cantón Palenque educational unit in the Province of Los Ríos in the first semester of 2018. In the research, a field study, descriptive cross section, quantitative modality for the realization of statistical analysis. The inductive and deductive methods were also used. Given the results obtained, it was determined that 53% of adolescents of 10 and 13 years old have already started their sexual life, 63% say they do not know the risks to which they are exposed, 20% do not know about contraceptive methods and 15 % indicates not having received information about sexuality. In this way it was possible to conclude that these are the main factors that contribute to adolescent pregnancies.